Transcriptome signature in young children with acute otitis media due to Streptococcus pneumoniae - Liu, Keyi (2012)
Streptococcus pneumoniae (Spn) is the predominant causative organism of acute otitis media in children. To better understand the genes that are regulated at the onset of AOM caused by Spn infection in the middle ear, the transcriptome profile of peripheral blood mononuclear cells isolated from children prior to and during an AOM event was evaluated by microarray. We found that 1903 (6.2%) of 29,187 genes were differentially regulated greater than 2 fold at the onset of AOM compared to the pre-infection stage of the same children. The ontology of differentially regulated genes was dominated by those involved with the immune response. At onset of infection, genes associated with bacterial defenses were significantly up-regulated, including beta-defensin123, S100 protein A12, Toll-like receptor 5, IL-10, and those involved in the classical and alternative complement pathways. Genes associated with inhibition of bacterial entry through clathrin-dependent endocytosis were also up-regulated. In contrast, genes associated with cell-mediated immune responses were broadly down regulated. The results provide the first human transcriptome data identifying genes differentially regulated at the onset of AOM in children.